2021
DOI: 10.1186/s12873-021-00509-0
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the ABCDE approach in relation to the method of instruction: a randomized controlled simulation study

Abstract: Background The Airway, Breathing, Circulation, Disability, and Exposure (ABCDE) approach is widely recommended and taught in many resuscitation courses. This study assessed the adherence to the ABCDE algorithm and whether this was affected by the instruction method used to teach this approach. Methods Randomized controlled trial in which simulation was used as investigational method. Between June 2017 and January 2018, neonatal healthcare providers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
1
7
0
1
Order By: Relevance
“…A study by Linders et al assessed adherence to the approach during neonatal advanced life support scenarios. In line with the present study, lower adherence among nurses compared to residents and specialists was found [ 6 ]. Possible explanations are potential differences between the in-hospital courses for different profession categories or less accredited courses for nurses compared to physicians.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A study by Linders et al assessed adherence to the approach during neonatal advanced life support scenarios. In line with the present study, lower adherence among nurses compared to residents and specialists was found [ 6 ]. Possible explanations are potential differences between the in-hospital courses for different profession categories or less accredited courses for nurses compared to physicians.…”
Section: Discussionsupporting
confidence: 92%
“…Despite efforts to increase awareness and knowledge of the ABCDE approach, adherence appears to be suboptimal [ 5 , 6 ]. According to Olgers et al, healthcare professionals in the Emergency Department used the ABCDE approach in only 33% of potentially unstable patients [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No presente estudo foi observado o uso do ABCDE, contudo percebe-se que apesar de haver 5 itens a serem avaliados segundo o protocolo, nem todo os itens foram avaliados, havendo cerca de 63% dos pacientes com avaliações incompletas através do instrumento, além ainda de a grande maioria das avaliações terem sido realizadas com a sequência incorreta. Tais resultados levantam novamente a preocupação quanto a qualidade do atendimento prestado às vítimas de trauma, uma vez que o ABCDE deveria ser implementado sob a premissa de aumentar a qualidade da avaliação e atendimento do paciente (THIM et al, 2012;SMITH;BOWDEN, 2017), a sua aplicação de forma incorreta e incompleta acaba por comprometer a acurácia do uso do mesmo (LINDERS et al, 2021).…”
Section: Discussionunclassified
“… 6 Moreover, as found by Linders et al, in their study, some factors may affect the application of the ABCDE approach as well as impede the reliance of healthcare workers on ABCDE; this include guidelines themselves, professional considerations, patient factors, team factors, incentives and also resources. 1 …”
Section: Introductionmentioning
confidence: 99%